Application of semi-analytical methods in production systems engineering serial lines - Ložar, Viktor; Abdulaj, Filip; Opetuk, Tihomir; Hadžić, Neven; Cajner, Hrvoje (2020)
Production lines can be designed by an analytical, semi-analytical, or numerical approach. This paper gives a brief introduction to the analytical approach of a single buffer line, the aggregation method, and the analytical approach of a multi-buffer line. An automotive paint shop production system will be used as a figurative example to compare the aggregation method and the recently developed analytical approach for a multi-buffer line. A discussion at the end will show the advantages and disadvantages of the analytical approach.
Bibliografija: 9 jed.
Summary.
Keywords: Proizvodno inženjerstvo -- Analitički pristup